A Microsoft Excel Spreadsheet for Selecting Organisational Improvement Initiatives based on Malaysia Business Excellence Framework and Industrial Revolution 4.0 - Mohammad, Musli; Nuar, Almalin; Yahya, Mohd Shahir (Research Progress in Mechanical and Manufacturing Engineering, 2021)
One type of the decision support tools that can be used to select appropriate organisational improvement initiatives is by using a Microsoft Excel spreadsheet. Organisational improvement initiatives involve approaches, technologies, management systems, techniques and/or tools, such as Lean, Cloud Computing, Quality Management System and Benchmarking. The objectives of this project are: (1) to identify the main organisational improvement initiatives based on Malaysia Business Excellence Framework (MBEF) and Industrial Revolution (IR) 4.0; (2) to investigate the existing Microsoft Excel Spreadsheets for the selection of organisational improvement initiatives; and (3) to develop a new version of a Microsoft Excel spreadsheet for selecting improvement initiatives. Data was collected using online questionnaire survey based on purposive sampling. The respondents of the survey involved consultants, managers and lecturers who are experts in the area related to operations and quality. The new version of Microsoft Excel spreadsheet consists of main interface, areas for improvement based on six enabler criteria of 2020-2025 MBEF (Leadership, Strategy, Information, Customer, Workforce and Process), examples of problems in the organisations, examples of improvement initiatives according to the MBEF, brief description of 73 organisational improvement initiatives (including IR 4.0 technologies), decision criteria, and summary report of the selection results. Based on the feedback from the survey, most of respondents agreed that the listed improvement initiatives are relevant, the spreadsheet is easy to use, the steps to complete the decision matrix are easy to follow, the selection criteria are suitable, the decision result are easy to understand and the Microsoft Excel spreadsheet can assist organisations in selecting appropriate improvement initiative.